Notes on the correct taxonomic status of Haliotis rugosa Lamarck, 1822, and Haliotis pustulata Reeve, 1846, with description of a new subspecies from Rodrigues Island, Mascarene Islands, Indian Ocean (Mollusca: Vetigastropoda: Haliotidae) - Owen, Buzz (Zootaxa, 2013)
Haliotis rugosa Lamarck, 1822, and H. pustulata Reeve, 1846, have long been a source of confusion. Herbert (1990) suggested the synonymy of the two and designated the lectotype and type locality of H. rugosa. Examination of several hundred shells of each of the two taxa has demonstrated that the H. rugosa morphology is found only on Mauritius and Reunion, while the H. pustulata morph occurs at Madagascar and the east coast of Africa, from approximately Park Rynie, South Africa, to the Red Sea and east to Yemen. No specimens from the latter localities resemble H. rugosa; however, a very small number of specimens from Mauritius have an intermediate morphology between the two taxa. The two species-level taxa are here considered as subspecies of each other. They show some overlapping shell morphology, but are geographically isolated.